RNase R is associated in a functional complex with the RhpA DEAD-box RNA helicase in Helicobacter pylori. Issue 9 (24th April 2021) - Tejada-Arranz, Alejandro; Matos, Rute G; Quentin, Yves; Bouilloux-Lafont, Maxime; Galtier, Eloïse; Briolat, Valérie; Kornobis, Etienne; Douché, Thibaut; Matondo, Mariette; Arraiano, Cecilia M; Raynal, Bertrand; De Reuse, Hilde
Abstract: Ribonucleases are central players in post-transcriptional regulation, a major level of gene expression regulation in all cells. Here, we characterized the 3′-5′ exoribonuclease RNase R from the bacterial pathogen Helicobacter pylori . The 'prototypical' Escherichia coli RNase R displays both exoribonuclease and helicase activities, but whether this latter RNA unwinding function is a general feature of bacterial RNase R had not been addressed. We observed that H. pylori Hp RNase R protein does not carry the domains responsible for helicase activity and accordingly the purified protein is unable to degrade in vitro RNA molecules with secondary structures. The lack of RNase R helicase domains is widespread among the Campylobacterota, which include Helicobacter and Campylobacter genera, and this loss occurred gradually during their evolution. An in vivo interaction between Hp RNase R and RhpA, the sole DEAD-box RNA helicase of H. pylori was discovered. Purified RhpA facilitates the degradation of double stranded RNA by Hp RNase R, showing that this complex is functional. Hp RNase R has a minor role in 5S rRNA maturation and few targets in H. pylori, all included in the RhpA regulon. We concluded that during evolution, Hp RNase R has co-opted the RhpA helicase to compensate for its lack of helicase activity.